Toxicogenetic monitoring in urban cities exposed to different airborne contaminants - Pereira, Tatiana S.; Beltrami, Laiana S.; Rocha, Jocelita A.V.; Broto, Francesc P.; Comellas, Lluis R.; Salvadori, Daisy Maria Favero [UNESP]; Vargas, Vera M.F. (Elsevier, 2013)
Microparticles found in the air may be associated with organic matter that contains several compounds, such as Polycyclic Aromatic Hydrocarbons (PAHs) and nitro-PAHs, and may pose a significant risk to human health, possibly leading to DNA mutations and cancers. This study associated genotoxicity assays for evaluating human exposure with the atmospheric air of two urban areas in southern Brazil, that received different atmospheric contributions. Site 1 was under urban-industrial influence and the other was a non-industrial reference, Site 2. Organic extracts from the airborne particulate matter were tested for mutagenicity via the Salmonella/microsome assay and analyzed for PAH composition. Cells samples of people residing in these two cities were evaluated using the comet and micronucleus assay (MN).Concentrations of the individual PAHs ranged from 0.01ng/m3 (benzo[a]anthracene) to 5.08ng/m3 (benzo[ghi]perylene). As to mutagenicity analysis of airborne, Site 1 presented all the mutagenic responses, which varied from 3.2±1.22rev/m3 (TA98 no S9) to 32.6±2.05rev/m3 (TA98, S9), while Site 2 ranged from negative to minimal responses. Site 1 presented a high quantity of nitro and amino derivatives of PAHs, and peaked at 56.0±3.68rev/μg (YG1024 strain). The two groups presented very low DNA damage levels without intergroup difference. Although Site 1 presented high mutagenic responses in the air samples, high PAH levels, healthy people exposed to this environment did not show significative damage in their genetic material. However, the evaluation of different environmental and genetic damage in such population is necessary to monitor possible damages. © 2013 Elsevier Inc.
Keywords: Comet assay; Human environmental exposure; Mutagenicity; Polycyclic aromatic hydrocarbon; Salmonella/microsome assay; Total airborne particulate matter; DNA; organic matter; polycyclic aromatic hydrocarbon; assay; atmospheric pollution; environmental risk; genotoxicity; health risk; mutagenicity; PAH; particulate matter; pollution exposure; public health; urban pollution; airborne particle; biological monitoring; Brazil; city; DNA damage; environmental factor; environmental monitoring; health hazard; heredity; microsome; Salmonella; toxicogenetics; urban area; Adolescent; Adult; Air Pollutants; Cities; DNA Damage; Humans; Mutagenicity Tests; Particulate Matter; Polycyclic Hydrocarbons, Aromatic; Young Adult